Landasan Fondasional Integrasi Keilmuan di UIN Maulana Malik Ibrahim Malang dan UIN Sunan Ampel Surabaya - Husniyatus Salamah Zainiyati (Islamica: Jurnal Studi Keislaman, 2015)
This article deals with the foundational base for integration of sciences trough interdisciplinary Islamic studies, with particular reference to UIN Malang and Surabaya. There are eleven IAINs/STAINs which have been transformed into UIN, each university has their own concept of developing Islamic knowledge. UIN Malang has the concept of pohon ilmu (the tree of sciences) and UIN Surabaya has the concept of integrated twin towers with three pillars. Although different in developing the concept, the two universities share the same perspective of perceiving the relation between general and religious sciences. The integration of science does not refer to the classification of its subject, but rather to the object of knowledge so that religious values can be transformed into different disciplines. It is hoped that in the long term UIN?with the foundation of the Qur??n and H}ad?th?can motivate the emergence of new sciences as blessing for the universe, or at least give new alternatives for the existing sciences, such as Islamic economics. The integration of sciences also needs to be articulated in learning models which are developed while emphasizing harmony between the intellectual tradition of higher education and local tradition of pesantrens.